EFEKTIVITAS PROGRAM PEMBERDAYAAN UMKM MELALUI RUMAH BUMN DALAM MENINGKATKAN PRODUKTIVITAS (Studi Kasus UMKM Binaan Rumah BUMN Sidrap) - Muhammad Ilham; Muh Tamrin; Rahman Yakub; Andi Riska Andreani Syafaruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of the Micro, Small, and Medium Enterprises (MSMEs) empowerment program implemented by Rumah BUMN Sidrap in improving the productivity of its assisted MSMEs. Rumah BUMN Sidrap, managed by PT Telkom Indonesia, provides various coaching programs including training, mentoring, business-legality facilitation, and digitalization for 260 assisted MSMEs, although the effectiveness of these programs has not been evenly distributed across all business sectors. This study employs a descriptive qualitative approach, with data collected through interviews, observation, documentation, and literature review. Eight informants participated, consisting of two facilitators and six assisted MSME actors selected through purposive sampling. Data were analyzed through data reduction, data display, and conclusion drawing/verification, assisted by NVivo 12 Pro software. The results show that the Rumah BUMN Sidrap empowerment program has run effectively, marked by the dominance of the real-change indicator (49%) in the empowerment variable and the work-quality indicator (48%) in the productivity variable. Meanwhile, improvements in work quantity and timeliness remain gradual due to limited capital and fluctuating market demand. These findings are expected to serve as input for Rumah BUMN Sidrap, local government, and MSME actors in designing more sustainable and targeted empowerment programs capable of enhancing MSME competitiveness.